No increase is detected and modeled for the seasonal cycle amplitude of δ13C of atmospheric carbon dioxide - F. Joos; F. Joos; S. Lienert; S. Lienert; S. Zaehle (Biogeosciences)
Measurements of the seasonal cycle of δ13C of atmospheric CO2 (δ13Ca) provide information on the global carbon cycle and the regulation of carbon and water fluxes by leaf stomatal openings on ecosystem and decadal scales. Land biosphere carbon exchange is the primary driver of δ13Ca seasonality in the Northern Hemisphere (NH). We use isotope-enabled simulations of the Bern3D-LPX (Land surface Processes and eXchanges) Earth system model of intermediate complexity and fossil fuel emission estimates with a model of atmospheric transport to simulate atmospheric δ13Ca at globally distributed monitoring sites. Unlike the observed growth of the seasonal amplitude of CO2 at northern sites, no significant temporal trend in the seasonal amplitude of δ13Ca was detected at most sites, consistent with the insignificant model trends. Comparing the preindustrial (1700) and modern (1982–2012) periods, the modeled small-amplitude changes at northern sites are linked to the near-equal increase in background atmospheric CO2 and the seasonal signal of the net atmosphere–land δ13C flux in the northern extratropical region, with no long-term temporal changes in the isotopic fractionation in these ecosystems dominated by C3 plants. The good data–model agreement in the seasonal amplitude of δ13Ca and in its decadal trend provides implicit support for the regulation of stomatal conductance by C3 plants towards intrinsic water use efficiency growing proportionally to atmospheric CO2 over recent decades. Disequilibrium fluxes contribute little to the seasonal amplitude of the net land isotope flux north of 40° N but contribute near equally to the isotopic flux associated with growing season net carbon uptake in tropical and Southern Hemisphere (SH) ecosystems, pointing to the importance of monitoring δ13Ca over these ecosystems. We propose applying seasonally resolved δ13Ca observations as an additional constraint for land biosphere models and underlying processes for improved projections of the anthropogenic carbon sink.